(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
The segment AL TV nas Comunidades, shown on the journalistic programming of TV Gazeta de Alagoas, aims to expose the problems faced by the community so that the Public Power can solve them. The present work aims to contextualize and delimit the production of journalistic information in the field of Information Science, based on constructions about the notions of information regime. This is a theoretical-conceptual discussion, part of a broader research, which is characterized as exploratory, carried out from bibliographical and documental surveys. It is considered that, in spite of the particularities, the production of the frame under analysis is conditioned by a series of elements, which conform the regime of production of journalistic information.